Modelling of tsunami-like wave run-up, breaking and impact on a vertical wall by SPH method - M. H. Dao; H. Xu; E. S. Chan; P. Tkalich (Natural Hazards and Earth System Sciences, 2013)
Accurate predictions of wave run-up and run-down are important for coastal impact assessment of relatively long waves such as tsunami or storm waves. Wave run-up is, however, a complex process involving nonlinear build-up of the wave front, intensive wave breaking and strong turbulent flow, making the numerical approximation challenging. Recent advanced modelling methodologies could help to overcome these numerical challenges. For a demonstration, we study run-up of non-breaking and breaking solitary waves on a vertical wall using two methods, an enhanced smoothed particle hydrodynamics (SPH) method and the traditional non-breaking nonlinear model Tunami-N2. The Tunami-N2 model fails to capture the evolution of steep waves at the proximity of breaking that was observed in the experiments. Whereas the SPH method successfully simulates the wave propagation, breaking, impact on structure and the reform and breaking processes of wave run-down. The study also indicates that inadequate approximation of the wave breaking could lead to significant under-predictions of wave height and impact pressure on structures. The SPH model shows potential applications for accurate impact assessments of wave run-up on to coastal structures.